2007
DOI: 10.1348/147608306x116016
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based cognitive therapy for residual depressive symptoms

Abstract: Group MBCT has a marked effect on residual depressive symptoms, which may be mediated through the mindfulness-based cognitive approach towards excessive negative ruminations in patients with residual depressive symptoms following a depressive episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(181 citation statements)
references
References 13 publications
10
159
1
11
Order By: Relevance
“…However, contrary to previous evidence suggesting that scores. This may be because most of this evidence is based on training in state mindfulness rather than trait mindfulness differences (e.g., Deyo et al 2009;Heeren and Philippot 2011;Kingston et al 2007). Although Borders et al (2010) reported an association with trait mindfulness, they measured mindfulness with the Mindfulness Attention Awareness Scale (Brown and Ryan 2003) and this scale has more in common with measures of attentional cognitive failures than with other measures of trait mindfulness (Cheyne, Carriere and Smilek 2006;Grossman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to previous evidence suggesting that scores. This may be because most of this evidence is based on training in state mindfulness rather than trait mindfulness differences (e.g., Deyo et al 2009;Heeren and Philippot 2011;Kingston et al 2007). Although Borders et al (2010) reported an association with trait mindfulness, they measured mindfulness with the Mindfulness Attention Awareness Scale (Brown and Ryan 2003) and this scale has more in common with measures of attentional cognitive failures than with other measures of trait mindfulness (Cheyne, Carriere and Smilek 2006;Grossman 2011).…”
Section: Discussionmentioning
confidence: 99%
“…43 Otra intervención el MBCT también mostró resultados prometedores al disminuir significativamente la rumiación excesiva en pacientes con SRD. 44 …”
Section: Terapia Cognitivo Conductual Basada En El Mindfulnessunclassified
“…Todo lo cual favorece las tasas de remisión y reduce las tasas de recaída/recurrencia. 32,35,36 Modelos psicoterapéuticos en el manejo de SRD Los cuatro modelos psicoterapéuticos utilizados como opción en el manejo de SRD son: Terapia cognitivo conductual, 16,37 Terapia del bienestar, 40 Terapia cognitivo conductual basada en el Mindfulness [42][43][44] y Terapia eutímica. 45 Todos fueron aplicados tras la remisión por tratamiento farmacoló-gico y ante la persistencia de SRD.…”
Section: Cuadrounclassified
See 1 more Smart Citation
“…Pacientes que já tiveram mais do que dois episódios depressivos anteriores, normalmente têm um prognóstico de 78% de uma nova recaída. O tratamento reduziu este índice a 36% (Ma e Teasdale, 2004), além de reduzir os sintomas residuais de depressão, principalmente aqueles relacionados com ruminação mental (Kingston et al, 2007).…”
Section: Prevenção De Recaída Na Depressãounclassified